Diálogos entre filosofia e religião na obra Pensamentos de Blaise Pascal: Fundamentos de uma antropologia desconcertante - SILVA, Romilson Ferreira da (2022)
The present research, of interdisciplinary nature, entitled Dialogues between philosophy and religion in the work Thoughts, of Blaise Pascal: foundations of a disconcerting anthropology, aims to understand the relationship between philosophy, religion and theology anthropology of this author, as well as to analyze the results of this link, seeking to therefore, in its first moment, to approach the historical context, in the guise of the foundations that allowed Pascal to develop his anthropology, appropriating the assumptions of the christian religion and reacting to rationalism and humanism, already matured in the 17th century. Then the anthropological perspective of Augustine of Hippo will be presented, one of Pascal's main references for the construction of his thinking about the human condition. Finally, the properly Pascalian anthropology will be thematized based on the relationship between philosophy and religion, explaining the paradoxical condition of the human being, described as great, but at the same time also as miserable, evidencing thus to follow the thinker, against the grain of modern humanism, proposing that human beings review their intentions and capacities, investing in self-knowledge, being able, through this movement, to find themselves in a situation of misery and despair. Seeing in God a way to recover its fullness. An alternative that is qualified in the present research as unusual and disconcerting, considering the deeply anthropocentric time in which it was written. In this way, it is intended to demonstrate that Pascal's anthropology develops a critique of the fragmented and deficient vision of man, provided by the privileged lens of the science of his time, denounced by the thinker as incapable of understanding all aspects of the human condition, criticism which in contemporary society, in which the gains and losses of an instrumental reason are still evaluated, still summons us.